Staying cool under pressure: Developing and maintaining emotional expertise in sport - Fawver, B.; Beatty, G. F.; Mann, D. T. Y.; Janelle, C. M. (Skill acquisition in sport: research, theory and practice, 2020)
The skills demonstrated by elite athletes across sports are thought by some to reflect innate talent supported by a continuous process of talent development. Scientists disagree as to the respective roles of innate talent and environmental determinants (e.g., Practice conditions) in accounting for skilled performance. However, ` there 15 agreement that expertise and expert performance result from some combination of dispositional proclivity (e.g., personality, physical traits), extended systematic training, and environmental influences (see Ericsson, Hoffman, Kozbelt, & Williams, 2018). These variables shape how skills are developed and refined. Virtually limitless combinations and complex interactions among these and other factors are possible, explaining the wide variability seen in performance outcomes. In this chapter, we focus on the influence of emotional reactions on skilled performance and the necessity for effective emotion regulation to realize expertise in sport. We integrate existing frameworks from the motor learning and sport psychology literature to consider how athletes attain key psychological and emotional skills. The premises of this chapter are fivefold: (1) optimal and suboptimal emotional states exist for the performance of sport skills; (2) individual, task specific, and environmental factors dictate emotional reactions; (3) emotional reactions can be regulated in adaptive and maladaptive ways; (4) proficiency in emotion regulation is critical for optimal skill learning and expert performance; and (5) emotion regulation is a skill that can be learned. Like other skills, we contend that emotion regulation can be acquired and refined through extended systematic practice. We provide evidence that the effectiveness of psychological skills is context-specific and dependent on the predominant objective, namely, to regulate emotion and/or to effectively perform motor tasks. We review empirical work an offer practical examples, as well as recommendations for future research in an effort to advance understanding of how to build a stress resistant, emotionally resilient athlete.